2010
DOI: 10.1021/np1003005
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation of the Antidiabetic Principle from Sorbus decora (Rosaceae) Used Traditionally by the Eeyou Istchee Cree First Nations

Abstract: Bioassay-guided fractionation of a crude extract (80% EtOH in H(2)O) of stem bark of Sorbus decora led the isolation of three new pentacycle triterpenes (compounds 1-3). The structures of 1-3 were established on the basis of spectroscopic methods (IR, HREIMS, 1D and 2D NMR) as 23,28-dihydroxyursan-12-ene-3β-caffeate, 23,28-dihydroxylupan-20(29)-ene-3β-caffeate, and 3β,23,28-trihydroxy-12-ursene, respectively. Compound 2 significantly enhanced glucose uptake in C2C12 cells, but compounds 1 and 3 did not. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…This enzyme, suggested as crucial in a plant’s adaptation to environmental cues and stresses (Winkel-Shirley, 2002; Chaves, Escudero & Gutierrez-Merino, 1997), is a major part of the plant’s response to UV-B radiation, drought and extreme temperature, all of which affect leaf structure more than bark (Chaves, Escudero & Gutierrez-Merino, 1997). The greater concentration of squalene synthase in the bark tissues of S. decora agrees with other findings that triterpenes, including those commonly identified within Sorbus, are often found in large concentration in the form of a resin within the inner bark (Guerrero-Analco et al, 2010; Hanson, 2003; Theis & Lerdau, 2003). While neither of the genes were found to be expressed significantly higher in the respective tissues of interest, we believe it is important to report these results as they demonstrate the utility of quantitative rtPCR in studying multiple genes from distinct tissues of plant of ethnobotanical, specifically medicinal, interest, and of this protocol for future studies into phytochemical evolution and action.…”
Section: Discussionsupporting
confidence: 89%
“…This enzyme, suggested as crucial in a plant’s adaptation to environmental cues and stresses (Winkel-Shirley, 2002; Chaves, Escudero & Gutierrez-Merino, 1997), is a major part of the plant’s response to UV-B radiation, drought and extreme temperature, all of which affect leaf structure more than bark (Chaves, Escudero & Gutierrez-Merino, 1997). The greater concentration of squalene synthase in the bark tissues of S. decora agrees with other findings that triterpenes, including those commonly identified within Sorbus, are often found in large concentration in the form of a resin within the inner bark (Guerrero-Analco et al, 2010; Hanson, 2003; Theis & Lerdau, 2003). While neither of the genes were found to be expressed significantly higher in the respective tissues of interest, we believe it is important to report these results as they demonstrate the utility of quantitative rtPCR in studying multiple genes from distinct tissues of plant of ethnobotanical, specifically medicinal, interest, and of this protocol for future studies into phytochemical evolution and action.…”
Section: Discussionsupporting
confidence: 89%
“…The biological activity of many plants, including Labrador tea, identified in the CEI pharmacopoeia for the treatment of symptoms related to T2D (Spoor et al 2006;Harbilas et al 2009;Saleem et al 2010) has been attributed to phenolic compounds (Eid et al 2010;Guerrero-Analco et al 2010;Harris et al 2012;Muhammad et al 2012;Shang et al 2012). Yet, the abundance and wide distribution of these plants across Eeyou Istchee and the boreal zone of Canada pose potential problems for quality control both for current traditional use and in the event that they may be transformed into natural health products for future use in communities.…”
Section: Introductionmentioning
confidence: 99%
“…In the 13 C NMR spectrum of 1, besides the nine carbon resonances ascribed to the pcoumaroyl moiety at δ C 166.1 (C, C-1'), 114.9 (CH, C-2'), 144.1 (CH, C-3'), 125.1 (C, C-4'), 130.7 (2 × CH, C-2' and 9'), 115.7 (2 × CH, C-6' and 8') and 159.6 (C, C-7'), the remaining 30 carbon signals were classified from DEPT and HSQC analysis into five methyls, ten alkyl methylenes, five alkyl methines, five alkyl quaternary carbons, three oxygen-bearing carbons (including two primary and one secondary) and two alkene carbons belonging to a disubstituted terminal double bond (Table 2). These NMR data suggested that 1 is an (E)-pcoumaroyl ester derived from the pentacyclic lupane-type triterpene, with the skeleton similar to those of the known oxygenated betulin analogues [7,12,13,15].In the HMBC spectrum, besides the correlations with C-4, C-23 and CH 3 -24, the low-field oxygenated methine proton at δ H 4.84 was also found to show a key correlation with C-1', the carbonyl carbon of the coumaroyl moiety. Consequently, it could be deduced that the esterification by a coumaric acid unit occurs at C-3.…”
Section: Resultsmentioning
confidence: 87%